2006
DOI: 10.1016/j.wocn.2005.08.001
|View full text |Cite
|
Sign up to set email alerts
|

An acoustic analysis of ‘happy-tensing’ in the Queen's Christmas broadcasts

Abstract: This paper presents a longitudinal analysis of some vowels from the annual Christmas broadcasts produced by Queen Elizabeth II over a 50-year period in order to investigate whether adults adapt to sound changes taking place in the community. The sound change that was analyzed in this paper, which is sometimes known as happY-tensing, concerns the tensing of the final vowel in words like 'happy' in British English Received Pronunciation over the course of the last 50 years. In the first part of the study, schwa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(102 citation statements)
references
References 52 publications
3
96
0
3
Order By: Relevance
“…4 An important assumption made here is that changes in the phonetic realization of forms are initiated by adult language users, and that these (possibly biased) forms form the input for language learners. This assumption is consistent with findings that phonetic realization of categories can indeed change over the lifetime (Harrington et al 2000;Harrington 2006;Sankoff and Blondeau 2007) but also allows for the fact that children often acquire qualitatively different grammars from those of their parents (Sankoff and Laberge 1973;Payne 1976Payne , 1980Hudson Cam and Newport 2005;cf. Foulkes and Vihman in press).…”
Section: Simulating Sound Change: Case Studiessupporting
confidence: 85%
“…4 An important assumption made here is that changes in the phonetic realization of forms are initiated by adult language users, and that these (possibly biased) forms form the input for language learners. This assumption is consistent with findings that phonetic realization of categories can indeed change over the lifetime (Harrington et al 2000;Harrington 2006;Sankoff and Blondeau 2007) but also allows for the fact that children often acquire qualitatively different grammars from those of their parents (Sankoff and Laberge 1973;Payne 1976Payne , 1980Hudson Cam and Newport 2005;cf. Foulkes and Vihman in press).…”
Section: Simulating Sound Change: Case Studiessupporting
confidence: 85%
“…There is rarely a reliable acoustic boundary between liquids and vowels (Lawson, Stuart-Smith, Scobbie, Yaeger-Dror & Maclagan 2011:81), so no attempt was made to place such a boundary, instead using a technique detailed below to capture vowel quality. The first two formants (F1, F2) were estimated across the labelled interval in Emu (Harrington 2010) via Linear Predictive Coding using a 45 ms Blackman window with 10 ms window shift. Formant values were overlaid on wideband spectrograms and any errors were corrected using Emu's formant correction tool.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Harrington (2006Harrington ( , 2007 showed that over a span of about 50 years, the lax vowel /ɪ/ in happy, as produced by HRH Queen Elizabeth II (in her annual Christmas addresses), developed tensing and thus converged towards the speech of ordinary people. Also, research shows that speakers mediate social distance (Giles and Coupland 1991) by adjusting their speaking styles.…”
Section: Perceptual Learning: Convergence and Divergencementioning
confidence: 99%